Effect of lasalocid and length of morning grazing on weight and shrink of steers grazing bromegrass pastures - K.P. Coffey; F.K. Brazle; Joseph L. Moyer (Kansas Agricultural Experiment Station Research Reports, 1994)
A total of 72 mixed breed steer s from two sources was used in an experiment to determine the effect of lasalocid and length of morning grazing prior to weighing on weight and shrink of steers grazing smooth bromegrass pastures. Steers were divided into eight groups and weighed at either 6, 7, 8, or 9 a.m. on 4 separate days. Half of the steers received a control mineral mixture and half received a mineral mixture containing lasalocid. Weights of purchased steers having an excitable disposition were not affected (P>.10) by length of morning grazing prior to weighing. However, weights of steers raised at the Southeast Kansas Branch Experiment Station (SEKES) increased with length of morning grazing. Steers allowed to graze for 3 hours before morning weighing had the lowest (P<.05) total % shrink and total % shrink/hour by 3 p.m. Lasaloid did not affect shrink. Using these figures, cattlemen could add additional weight to cattle by simply allowing them to graze longer before gathering them for sale.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Shrink; Steers; Grazing time; Marketing